Follow-up of infants with congenital hypothyroidism and low total thyroxine/thyroid stimulating hormone on newborn screen - Quinn McCormick; Leslie Pitts; Zachary Hughes (Korean Society of Pediatric Endocrinology, 2019)
Purpose Newborn screening (NBS) methods to detect congenital hypothyroidism (CH) vary regarding whether total thyroxine (T4), thyroid stimulating hormone (TSH), or both are measured. Neonates with low T4 and normal or low TSH (lowT4/TSH) may only be detected by T4-inclusive methods or age-dependent repeat screens. Premature neonates and those with pituitary-hypothalamic disorders frequently manifest lowT4/TSH. Methods This is a retrospective case-study of newborns who were screen-positive for lowT4/TSH in Alabama in 2009-2016 using a combined T4 and TSH method and 2 routine NBS. The clinical, laboratory, and final diagnosis after 3 years were determined. Results Over 8 years, 225 infants were referred to our institution for evaluation and treatment of CH. Twelve infants were screen-positive for lowT4/TSH by first or second NBS. Four of the 12 infants had permanent CH (30%): 2 with primary and 2 with central etiologies. One infant with moderately severe central CH was only detected by the routine second NBS. Six of 7 premature infants had elevated TSH on serum confirmation labs consistent with a delay in hypothalamic-pituitary maturation, yet 2 of these patients were later established to have permanent primary CH. While most cases of lowT4/TSH resolved by 3 years of age, several neonates had extended periods of moderate to severe hypothyroxinemia prior to detection and treatment. Conclusions One third of the infants with lowT4/TSH on NBS in this study had permanent CH. These results emphasize the importance of T4-based assay methods, subsequent (repeat) screens and long-term follow-up in the management of neonates with lowT4/TSH on newborn screen.